Asymptotic expansion of the characteristic function of the sum ∑φ(2^k t) - Misevičius, G. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. А. Мисявичюс. Асимптотическое разложение для характеристических функций сумм вида ∑φ(2^k t) G. Misevičius. Sumų ∑φ(2^k t) charakteringųjų funkcijų asimptotinis išdėstymas